Evaluation and follow-up of patients diagnosed with hypophysitis: A cohort study - Hacıoğlu, Ayşa; Karaca, Züleyha; Uysal, Serhat; Özkaya, Hande Mefkure; Kadıoğlu, Pınar; Soyluk Selçukbiricik, Özlem; Gül, Nurdan; Yarman, Sema; Köksalan, Damla; Selek, Alev; Cantürk, Zeynep; Çetinarslan, Berrin; et al. (My University, 2024)
Objective: Primary hypophysitis might be challenging to diagnose, and there is a lack of evidence regarding optimal treatment strategies due to rarity of the disease. We aim to investigate the clinical features and compare the outcomes of different management strategies of primary hypophysitis in a large group of patients recruited on a nationwide basis. Design: A retrospective observational study. Methods: The demographic, clinical, and radiologic features and follow-up data were collected in study protocol templates and analyzed. Results: One hundred and thirteen patients (78.8% female, median age: 36 years) were included. Lymphocytic (46.7%) and granulomatous hypophysitis (35.6%) were the prevailing subtypes out of 45 patients diagnosed after pathologic investigations. Headache (75.8%) was the most common symptom, and central hypogonadism (49.5%) was the most common hormone insufficiency. Of the patients, 52.2% were clinically observed without interventions, 18.6% were started on glucocorticoid therapy, and 29.2% underwent surgery at presentation. Headache, suprasellar extension, and chiasmal compression were more common among glucocorticoid-treated patients than who were observed. Cox regression analysis revealed higher hormonal and radiologic improvement rates in the glucocorticoid-treated group than observation group (hazard ratio, 4.60; 95% CI, 1.62-12.84 and HR, 3.1; 95% CI, 1.40-6.68, respectively). The main indication for surgery was the inability to exclude a pituitary adenoma in the presence of compression symptoms, with a recurrence rate of 9%. Conclusion: The rate of spontaneous improvement might justify observation in mild cases. Glucocorticoids proved superior to observation in terms of hormonal and radiologic improvements. Surgery may not be curative and might be considered in indeterminate, treatment-resistant, or severe cases.
Keywords: Adrenal Insufficiency; Glucocorticoids; Hypogonadism; Hypophysitis; Observation